2007
DOI: 10.1108/14678040710748058
|View full text |Cite
|
Sign up to set email alerts
|

Performance and usability testing of multidimensional taxonomy in web site search and navigation

Abstract: Purpose -Development of an effective search system and interface largely depends on usability studies. The aim of this paper is to present the results of an empirical evaluation of a prototype web site search and browsing tool based on multidimensional taxonomies derived from the use of faceted classification. Design/methodology/approach -A prototype Faceted Classification System (FCS), which classifies and organizes web documents under different facets (orthogonal sets of categories), was implemented on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Libraries had either implemented a new product, or they were thinking about Uddin and Janacek asked nineteen users (staff and students at the Asian Institute of Technology) to use a website search engine with both a traditional results list and a faceted results list. 22 Tasks were as follows: (1) look for scholarship information for a masters program, (2) look for staff recruitment information, and (3) look for research and associated faculty member information within your interested area. 23 They found that users were faster when using the faceted system, significantly so for two of the three tasks.…”
Section: ■ ■ Resultsmentioning
confidence: 99%
“…Libraries had either implemented a new product, or they were thinking about Uddin and Janacek asked nineteen users (staff and students at the Asian Institute of Technology) to use a website search engine with both a traditional results list and a faceted results list. 22 Tasks were as follows: (1) look for scholarship information for a masters program, (2) look for staff recruitment information, and (3) look for research and associated faculty member information within your interested area. 23 They found that users were faster when using the faceted system, significantly so for two of the three tasks.…”
Section: ■ ■ Resultsmentioning
confidence: 99%
“…The hierarchical navigation through the Simple Knowledge Organization System Reference -SKOS modelling scheme, inside a DL, is a crucial operation in terms of narrowing the obtained results [2], [10]- [12]. However, browsing the taxonomic levels increases the complexity of the interactivity and usability of any search interface [13].…”
Section: Related Workmentioning
confidence: 99%